The Effect of Teacher Social Support on Students’ Academic Hardiness at SMPN 2 Sindue Tobata - Della Adelia Sawitri; Munifah Munifah; Dian Fitriani; Ikhlas Rasido (MASI Mandiri Edukasi, 2025)
This study aims to determine the effect of teacher social support on students’ academic hardiness at SMPN 2 Sindue Tobata. The research employed a descriptive, quantitative approach with saturated sampling, involving all 108 students enrolled in the 2025/2026 academic year. Data were collected using validated Likert-scale questionnaires on teacher social support and academic hardiness, both of which demonstrated good reliability (α = 0.944 and α = 0.780). Data analysis employed descriptive statistics and simple linear regression using SPSS version 27. The findings revealed that 95.4% of students perceived high levels of teacher social support, and 71.3% exhibited very high academic hardiness. Regression results indicated a positive and significant influence of teacher social support on academic hardiness (t = 3.885, p < 0.05), with a regression coefficient of 0.460. These results suggest that increased social support from teachers enhances students’ ability to manage academic stress, remain committed, and view learning challenges as opportunities for growth. The study underscores the importance of strengthening teacher–student relationships to foster resilience and motivation in learning environments.